RESEARCH OF WHEEL TREAD WEAR AND FATIGUE BASED ON ALE METHOD - ZHOU Xun; YU CaiDong; YANG LiuQing; GAO Yun; HU Ming; CHEN WenHua (Jixie qiangdu)
Apply Arbitrary Lagrangian Eulerian（ ALE） and Archard wear theory to establish wheel wear analysis model of CRH5,by finite element static and steady state analysis,combined with repair operations to obtain the wheel wear law under typical conditions,including dynamic distribution regularity along the surface of the wheel tread wear degree and wear volume.Fatigue life of the worn wheel was also studied based on steady state analysis to get the evolutional law of the fatigue damage rate of wheel changing with the amount of wear. The results show that the fatigue damage rate of the wheel is significantly decline initially however being steady when it’s over 70% of the whole simulation wear loss.